Decision Analysis of Surgical Treatment Indications for Metastatic Epidural Spinal Cord Compression - Pahuta, Markian (Université d'Ottawa / University of Ottawa, 2019)
Metastatic epidural spinal cord compression (MESCC) occurs when tumour invades the epidural space and compresses the spinal cord. Despite Level 1 evidence that surgery is the most effective treatment for MESCC, there is controversy regarding the role of surgery because of fear that patients who have a short survival will spend a large fraction of their remaining life recovering from surgery and potential complications. This controversy could be resolved by decision-analysis of MESCC treatments using quality-adjusted-life-years (QALYs). There have been two barriers to conducting decision-analysis of QALYs for MESCC: (a) lack of utility data, and (b) skepticism regarding decision-analysis. The first four research chapters in this thesis address these barriers. The final research chapter reports a decision-analysis of QALYs on the role of surgery in MESCC. Chapter 1 provides background information on the controversy regarding surgical treatment for MESCC and the rationale for each of the subsequent chapters. Chapter 2 reports a psychometric validation study of a web-based utility valuation module for MESCC. In Chapter 3, application of this module to a general population utility valuation study with a market research panel is described. In Chapter 4, the beneficial properties of Bayesian statistical analysis to minimizing “arbitrariness” in probabilistic sensitivity analysis are described in relation to prognostication for MESCC. Chapter 5 presents a strategy for simplifying and enhancing the transparency of Markov cohort simulation. Finally, the work presented in the research chapters is applied in Chapter 6 to conduct Markov cohort simulation to determine if patients with short survival derive net health-related quality-of-life benefit from surgery. Pragmatic research around barriers to decision-analysis of QALYs for MESCC was conducted to resolve the controversy regarding the role of surgery in the treatment of MESCC. Under most circumstances, MESCC patients who can ambulate prior to treatment derive net HRQoL benefit from surgery, even if prognosis is poor. Non-ambulatory patients can derive net HRQoL benefit but only if the morbidity of surgery is relatively low. It is my hope that the work used to address barriers to decision-analysis of QALYs will be disseminated and applied in other clinical problems.
Keywords: Metastatic Disease; Spinal Cord Injury; Decision Analysis; Quality of Life; Decision Analysis